Valuation devices and the dynamic legitimacy-performativity nexus: The case of PEP in the English legal profession - Faulconbridge, James R.; Muzio, Daniel (Accounting, Organizations and Society, 2021)
Existing studies have developed increasingly sophisticated accounts of the performative agency of valuation devices and their effects on markets and organizations. In particular, research has focused on the work of different actors to legitimize valuation devices and ensure their adoption, which then leads to performativity. This paper extends work on the legitimacy and performativity of valuation devices by developing a dynamic, non-linear theorization of the boundary conditions of performativity and the feedbacks that result in changes in performativity over time. We ask: How do evolutions in a valuation device’s legitimacy relate to its performativity? Our analysis is based on a longitudinal study of the profits per equity partner (PEP) metric which between 1995 and 2013 became established as a key valuation device for English law firms. Through this case we draw attention to the dynamic legitimacy-performativity nexus . We show how the waxing and waning of different forms of legitimacy, in line with the dynamics of the broader institutional environment, affect the performativity of a particular valuation device. We also reveal a performativity paradox . The more a device gains legitimacy the more it becomes influential and exercises performative effects. The more this happens, the more the risk that tensions, contradictions and challenges will arise and begin to undermine the valuation device’s legitimacy and consequently its performativity. Consequently, we contribute to better theorizing the dynamic links between legitimacy, performativity and counter-performativity.